2020
DOI: 10.1080/00380768.2020.1816444
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intercropping component of conservation agriculture on sorghum yield in the Sudan Savanna

Abstract: Conservation agriculture (CA), which consists of minimum soil disturbance, soil cover, and crop rotation/ association, has been promoted as an indivisible three-component package to control water erosion in the Sudan Savanna. However, CA has not been adopted by local smallholder farmers, probably because the three-component package constitutes a large burden for the farmers. Our previous study revealed that two components-minimum tillage and crop residue mulching-are sufficient for soil conservation and interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…As a result, the seed weight increased. The increasing harvest index, according to Ikazaki et al (2020), could be associated with higher whole plant nitrogen and higher nitrogen translocation efficiency. The increased of dry weight accumulation in the tolerant group compared to the intolerant group indicated that tolerant soybeans have a higher capacity for high dry matter accumulation during harvest.…”
Section: Total Biomass (7 Wap and Harvest) And Harvest Indexmentioning
confidence: 99%
“…As a result, the seed weight increased. The increasing harvest index, according to Ikazaki et al (2020), could be associated with higher whole plant nitrogen and higher nitrogen translocation efficiency. The increased of dry weight accumulation in the tolerant group compared to the intolerant group indicated that tolerant soybeans have a higher capacity for high dry matter accumulation during harvest.…”
Section: Total Biomass (7 Wap and Harvest) And Harvest Indexmentioning
confidence: 99%
“…Summer crop production in South Africa is shifting from current production areas due to changes in rainfall and temperature regimes (Weepener et al, 2014). Sorghum thrives on low fertility soils with limited inputs for food and industrial use in breweries, production of animal feed, and as feedstock for biofuel production (Meki et al, 2013;Ikazaki et al, 2020). Moreover, sorghum is the fifth most important cereal crop after wheat (Triticum aestivum), rice (Oryza sativa), maize (Zea mays) and barley (Hordeum vulgare) (Bakari et al, 2023) with high tolerance to heat and drought.…”
Section: Introductionmentioning
confidence: 99%